Using Clil Technology in Mathematics Lessons - Matupayeva Sh. Z. (Euro Asian Journal Publishing, 2024)
Mathematical CLIL – adaptation of CLIL to mathematics. Mathematics is often described as a subject with its own language. Therefore, "CLIL" mathematics teachers teach not only the subject itself, but also two languages - the language of mathematics and a second or foreign language.
Keywords: Mathematics; symbols; visual aids; text; reasoning